Influencing factors and outcomes of entrepreneurial activities in German healthcare organizations – a qualitative study. (3rd July 2021) - Brandt, Florian; Znotka, Matti
ABSTRACT: Demographic, societal and medical-technical changes together with a continuous cost increase propose substantial challenges to healthcare systems. To mitigate the persistent challenges, we propose solutions offered by entrepreneurial activities and innovative forces. Entrepreneurial activities are a key element of economic performance and are vital to ensure a sustainable healthcare system. However entrepreneurial development proceeds slowly in the healthcare sector. Based on the concept of Entrepreneurial Orientation (EO), which regularly is described by the dimensions innovativeness, proactiveness and risk-taking, we developed relevant knowledge by interviewing selected experts in German healthcare organizations. To find out more about obstacles and stimuli of entrepreneurial activities, data collection focused on respective influencing factors. Furthermore, outcomes of entrepreneurial activities were investigated. The data were analysed using qualitative content analysis. Ultimately it is shown that governmental and intra-organizational regulation frequently impedes entrepreneurial activities. Stimuli of entrepreneurial activities may derive from the market environment and competitive constraints, financial incentives, technological and social development, autonomy of involved actors, and an entrepreneurial and collaborative mindset of healthcare leaders, policy makers and employees. If entrepreneurial activities were undertaken, they regularly aim to improve quality and efficiency of healthcare. Therefore, it is vital to create an entrepreneurial environment to ensure innovative developments.